Hybrid artificial intelligence systems : 9th International Conference, HAIS 2014, Salamanca, Spain, June 11-13, 2014. Proceedings - Carvalho, Andre C. P. L. F.; Pan, Jeng-Shyang; Wozniak, Michał; Quintian, Hector; Corchado, Emilio; Polycarpou, Marios (Lecture Notes in Computer Science, 2014)
This volume constitutes the proceedings of the 9th International Conference on Hybrid Artificial Intelligent Systems, HAIS 2014, held in Salamanca, Spain, in June 2014. The 61 papers published in this volume were carefully reviewed and selected from 199 submissions. They are organized in topical sessions on HAIS applications; data mining and knowledge discovery; video and image analysis; bio-inspired models and evolutionary computation; learning algorithms; hybrid intelligent systems for data mining and applications and classification and cluster analysis.